Simulação de um aquecedor solar de água como etapa do processo de destoxicação da torta de mamona. - Silva, Josenildo Araujo da (2007)
Algorithms have been developed in arder to simulate the water solar heating as a strategy for lowering castor bean pie destoxication costs, among from the biodiesel oil for production extraction processo Diverse procedure, substances solubilization, this residue toxic caracter factor, found in hot water and in some saline solutions, motivated this water heating modeling work, through solar energy, since this procedure type can and low cost to the above-mentioned methods, on account of this, one has used computational smulink/matlab in arder to simulate and to arise favorable conditions for this technique use strategies elaboration. One has, then, analized several situation, departing from a termal heating proposal, since this is a less expensive heat transference formo Of this form an objective function was proposal to create O variable that esteem the behavior of the system and better define the excellent conditions for the considered processo .Among these, the established variable as parameters for the simulated conditions, are presented the results, taking itself in account values of income for the process, existing in literature. One porpuses dynamic models, under complexity different degress, for a water heating process previous evaluation, through solar energy. Temperature variations, in the process diferrent stages, have been simulated, with simulink/matlab aid for the above-mentioned system behaviour analysis one presents computational models. blocks diagrams, correspondent to each one of the elaboration stage. Proposed mathematical models provided important previsions for temperature values, in the above-mentioned system different components, resulting as a work important tool for a next stage which is that one of the optimization.